67 ANALISIS EFEKTIVITAS PERLAKUAN INDEPENDENSI AKUNTAN PUBLIK DALAM MEMBANGUN KUALITAS AUDIT (Studi Empiris pada Kantor Akuntan Publik di Jakarta) - -, Amilin; Halomoan, Hery (Jurnal Manajemen dan Keuangan, 2008)
The research has purpose to analyze the effectiveness of independence by public accountants to build auditâs quality. This research uses qualitative descriptive method with âImportance and Performance Analysisâ it analyze level of performance and importance which is result the data in cartesius diagram about independenceâs factors which is building auditâs quality. The data resulted by spreading questioner toward 42 public accountants which are work in public accountant office.The result research of research shows that the answer whit level of appropriateness between performance and importance is 95.25%. It means that the public accountants have independent when audited because it has appropriate whit respondent expectation. The performance of independence effectively about 75.64% respondent show effective.Keyword : effectiveness, public accountantâs independency, auditâs quality